2010
DOI: 10.1021/jp909531s
|View full text |Cite
|
Sign up to set email alerts
|

Water-Induced Relaxation of a Degenerate Vibration of Guanidinium Using 2D IR Echo Spectroscopy

Abstract: The nearly degenerate asymmetric stretch vibrations near 1600 cm −1 of the guanidinium cation in D-glycerol/D 2 O mixtures having different viscosity were studied by 2D IR photon echo spectroscopy. The polarization dependent photon echo signal shows two separate frequency distributions in the 2D spectrum in D 2 O, even though only one band is evident from inspection of the linear FTIR spectrum. The split components are more clearly seen at higher viscosity. The interactions with solvent induce energy transfer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
81
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(90 citation statements)
references
References 41 publications
8
81
0
1
Order By: Relevance
“…In a study of guanidinium in water and water-glycerol mixtures, Hochstrasser and coworkers have recently analyzed in detail the effects of excitation versus energy transfer on the anisotropy of 2D-IR and dispersed photon echo signals of a quasi-degenerate mode 23 . They concluded that in their case fast anisotropy decay is primarily caused by excitation transfer, whereas reorientation of the transition dipole moments is slower.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study of guanidinium in water and water-glycerol mixtures, Hochstrasser and coworkers have recently analyzed in detail the effects of excitation versus energy transfer on the anisotropy of 2D-IR and dispersed photon echo signals of a quasi-degenerate mode 23 . They concluded that in their case fast anisotropy decay is primarily caused by excitation transfer, whereas reorientation of the transition dipole moments is slower.…”
Section: Discussionmentioning
confidence: 99%
“…A similar approach was recently taken by Hochstrasser and co-workers, who investigated the water-induced relaxation of Guanidinium (D 3 -symmetry). 23 Compared to their study, the nitrate ion offers the advantage of a much larger solvent-induced splitting of the degenerate vibrations, already in pure water (see below), which also allows us to better differentiate between excitation transfer and normal mode mixing processes.…”
Section: Introductionmentioning
confidence: 99%
“…However, to the best of our knowledge, the concept of a CI has not been used in the context of vibrational adiabatic states. Jahn-Teller type of coupling has been discussed in the context of vibrational transitions [24,25], which in fact leads to a CI dictated by symmetry, but that connection has not been made. In this Letter, we derive the conditions that such an intersection occurs, present quantum-dynamical model calculations to show the consequences for the vibrational dynamics and spectra, and demonstrate via ab initio calculations that low-lying vibrational CIs indeed exist in concrete molecular systems.…”
mentioning
confidence: 99%
“…We require at least two HF modes to assure that two vibrational states may become degenerate, either by symmetry via a Jahn-Teller type of coupling [24,25] or accidentally (which is the case we will focus on). On the other hand, at least two LF modes are needed because the hypersurface of a CI is N -2-dimensional (N being the number of LF modes).…”
mentioning
confidence: 99%
“…2,3 Due to the sensitivity to local environment and time resolution, ultrafast vibrational spectroscopy is now the method of choice for studying rapid dynamical processes of molecular ions in water. [4][5][6] Several different ions have been investigated using time resolved vibrational spectroscopy (e.g., cyanide, 7,8 azide, 9, 10 thyocyanate, 11 guanidinium, 12,13 trifluoroacetate, 14 tricyanomethanide, 6 etc.). However, only a few studies have focused directly on the effect of the water motions, when the a) Authors to whom correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%